Social emotional learning at global islamic school 3 yogyakarta: challenges and solutions - Muthmainah, Muthmainah; Mashar, Riana; Sari, Tuti Puspita (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2024)
Background: Social Emotional Learning (SEL) has become an important part that needs to be accomplished from an early age. However, the issue of implementing learning in kindergarten has not been widely researched, especially when viewed from the challenges and solutions for teachers. Social emotional learning is an important agenda at GIS 3 Yogyakarta to lay a solid foundation for children's personality and behavior.Aim: This research aims to examine the challenges and solutions for SEL at Global Islamic School 3 Yogyakarta.Method: This study employed qualitative methods with semi-structured interviews of five teachers. Data analysis includes the process of data collection, data condensation, data presentation, and drawing conclusions/verification. The validity of the data was tested through source triangulation and technical triangulation.Results: The results of the research show that the challenges faced by teachers are the exclusive environment for children, parental care, and lack of control over the use of gadgets. Next, the teacher determines a solution, namely implementing various activities such as morning sharing, class agreements, taking turns appearing in front of the class, new and exciting games, giving reward stars, group work, circle time, market day, show and tell, cooperative games, reading stories or fairy tales, projects with parents, school habituation programs, as well as parenting and collaborating with parents regarding children's use of gadgets. Creative teachers are prudent. They have good personal and professional well-being. Conclution: Collaboration with parents needs to be improved so that social-emotional abilities increase.